A4NH 2016 annual report - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2017)
In its fifth and final year of Phase I, the CGIAR Research Program on Agriculture for Nutrition and Health (A4NH) has validated its core areas of research, taking many to scale while also broadening its Phase II portfolio. By the end of 2016, more than 130 biofortified varieties of 10 crops were released in over 30 countries, all positive steps toward HarvestPlus’s goal of reaching 20 million farm households with biofortified crops by 2020 and 1 billion people consuming biofortified foods by 2030. High quality evidence—on topics such as emerging zoonoses, Rift Valley fever, aflatoxin control, and food safety in informal markets—helped inform policy and decision making to prevent and control agriculture-associated diseases in high-risk areas. Following a successful Nigeria pilot stage, the aflasafe™ approach for managing aflatoxins consistently reduced groundnut and maize aflatoxin contamination by at least 80 percent, with plans and investments to expand the approach to 11 other African countries. Rigorous evaluations of integrated agriculture-nutrition interventions demonstrated, for the first time, that well-designed programs can have measurable impacts on child and maternal nutrition, as well as on women’s empowerment.